Influence of Service Quality Dimensions of Islamic Banks on Customer Satisfaction and Their Impact on Customer Loyalty - Afifah, A; Kurniawati, Nurul Alfiah (Journal of Islamic Economic Laws, 2021)
Strengthening Islamic banking funding is one of particular strategies in the Indonesian Islamic banking master plan for 2019-2024, as one of their expected outputs is to increase market share and customer satisfaction of Islamic banks. This study aims to identify influence of service quality dimensions on customer satisfaction and their impacts on customer loyalty in Islamic banks in Indonesia. This study used a quantitative approach. Its data were collected by an online questionnaire with five Likert scales randomly given to 136 customers from several Islamic banks who had direct transactions at the Islamic banks. The sampling technique of this study used a purposive sampling technique, and its analysis technique used Structural Equation Modeling based on Partial Least Square (SEM-PLS). The findings of this paper indicate that the dimensions of both compliance and responsiveness have significant influence on customer satisfaction and customer loyalty. Meanwhile, assurance, reliability, and empathy dimensions have no significant impacts on customer satisfaction and customer loyalty. Tangible dimension has significant influence on customer satisfaction but has no significant influence on customer loyalty. Customer satisfaction has a significant impact on customer loyalty.